Analysis of Communication Patterns Between Chinese and Sundanese Ethnic in Suryakencana, Bogor - Nathalia Perdhani Soemantri; Muthia Karina; Aprilyanti Pratiwi; Rosmalia Ahmad (CoverAge: Journal of Strategic Communication, 2023)
Chinese ethnic live for generation across Indonesia and have adapt with Indonesian culture. in Bogor City, West Java. In general, Chinese ethnic descent who live in Bogor, West Java, specifically in Central Bogor sub-district live in Warehouse and Pasar Babakan sub-districts which include the Suryakencana area, with a percentage of 27%, live side to side with Sundanese ethnicity. The purpose of this study was to determine communication patterns between ethnic groups of Chinese and Sundanese descent on Jalan Suryakencana Bogor. This study combines two main concepts: cross-cultural communication and communication patterns. This study is using interpretif paradigm with a qualitative descriptive approach. Data collection uses three methods: in-depth interviews, and non-participatory observation. The study findings reveal that cross-cultural communication emerges through tolerance, especially in terms of respect, openness, association, and acculturation. The ethnic identity of Chinese descent is reflected in architectural features decorated with traditional Chinese elements, wedding practices, and Chinese vocabulary in daily conversation. Interpersonal communication patterns emerge in trading contexts, while group communication patterns emerge during social activities.